The Influence of the Two Stay Type Cooperative Learning Model Two Stray on Mathematics Learning Outcomes Students of MTS PAB 1 Helvetia - Syahputri, Novita; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine the effect of the Two Stay Two Stray type of cooperative learning model on students' mathematics learning outcomes. The research was carried out at MTs PAB 1 Helvetia with 32 students in class VIII-B as the experimental class. This research is a quantitative research with experimental method using one group pretest posttest design. Students are given a test to measure learning outcomes and an observation sheet to measure student activity. From the results of the study, the average pretest value was 49.6875 and the posttest average value was 8.0938. The results of the hypothesis test carried out show that the value of t_count is , with the value of t_table at a significant level of 0.05, which is 1.694, then t_count ( ) > t_table (1.694). The gain index value of 0.71678 is interpreted into the criteria for the value of g>0.7, the results indicate that the gain index is in the high category. The conclusion of this study explains that there is an effect of the Two Stay Two Stray type of cooperative learning model on students' mathematics learning outcomes where there is an increase in the average value of learning outcomes after being taught using the Two Stay Two Stray type of cooperative learning model, and student activities are quite active during the process. learning using the type of cooperative learning model Two Stay Two Stray